2021
DOI: 10.17221/145/2021-agricecon
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural production trends towards carbon neutrality in response to the EU 2030 Green Deal: Economic and environmental analysis in horticulture

Abstract: The European Green Deal to tackle climate change sets emission reduction targets for 2050. Particular attention has been paid to the agricultural sector, where there is a strong need to reduce carbon emissions and re-establish the natural carbon cycles. The concept of carbon neutrality is emerging in a scenario where it is necessary to reduce carbon dioxide (CO<sub>2</sub>) emissions from cultivation to near zero. The quantification of carbon emissions was carried out by the carbon footprint (CF) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The studies on climate efficiency available in the literature are linked mainly with efficiency assessment of the concept in the particular field of industry [11,16,17] or pertain generally to, for example, renewable energy sources, energy demand reductions, or energy efficiency improvements [22][23][24][25]. Another well-represented field of research pertains to the analysis of energy efficiency dependency and economic growth [27][28][29]31,32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies on climate efficiency available in the literature are linked mainly with efficiency assessment of the concept in the particular field of industry [11,16,17] or pertain generally to, for example, renewable energy sources, energy demand reductions, or energy efficiency improvements [22][23][24][25]. Another well-represented field of research pertains to the analysis of energy efficiency dependency and economic growth [27][28][29]31,32].…”
Section: Discussionmentioning
confidence: 99%
“…A broad review of research on carbon neutrality, drawing attention to the issue in different areas and economic sectors, has been developed. W ąs et al (2021) [11] , analyzed the impact of greenhouse gas emission reductions in farm sector in Poland; Becker et al (2020) [16] showed benefits of reducing emissions in the French spirits sector; and the research of Scuderi et al (2021) [17] concentrated on carbon footprint in conventional, organic, and zero-residue potato cultivation in Sicily. The research of Franzoi et al (2021) [18] and Carcassi et al (2021) [19] concerns neutrality in construction.…”
mentioning
confidence: 99%
“…Agricultural production activities produce a large amount of greenhouse gases, and their impact is second only to industrial carbon emissions, making agricultural emission reductions imperative (Scuderi et al, 2021). Scholars have used Kaya constant equation, LMDI factor decomposition, STIRPAT model, Divisia index decomposition, ARDL model, VAR model, and GWR model to study the factors influencing agricultural carbon emissions (Li et al, 2014;Akram et al, 2019;Aziz et al, 2022;Yan et al, 2017;Koondhar et al, 2021;Guo et al, 2022;Han et al,2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Fossil fuels contribute to global warming, which is a major problem in various parts of the world. Many countries plan to reduce carbon dioxide gas emissions towards a carbon neutral country by 2030 [1][2][3].…”
Section: Introductionmentioning
confidence: 99%